DOSY NMR and MALDI‐TOF evidence of covalent binding the DNA duplex by trimethylammonium salts of topotecan upon near UV irradiation. (27th May 2015) - Naumczuk, Beata; Hyz, Karolina; Kawęcki, Robert; Bocian, Wojciech; Bednarek, Elżbieta; Sitkowski, Jerzy; Wielgus, Ewelina; Kozerski, Lech
Abstract : Using DOSY NMR and MALDI‐TOF MS techniques, we present evidence that quaternary trimethylammonium salts of topotecan, [TPT‐NMe3 ] + X − (X = CF3 SO3, HCOO), bind covalently the natural DNA oligomer upon near UV irradiation in water under physiological conditions. It is shown that formate salt is very reactive at pH 7 and requires short irradiation time. This weak irradiation at 365 nm paves the way for a new application of TPT derivatives in clinical use, which can dramatically increase the therapeutic effects of a medicine. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Using DOSY NMR and MALDI‐TOF MS techniques, we present evidence that quaternary trimethylammonium salts of Topotecan, [TPT‐NMe3 ] + X − (X = CF3 SO3, HCOO), bind covalently the natural DNA oligomer upon near UV irradiation in water under physiological conditions. This paves the way to a new application of TPT derivatives in clinical use, which can dramatically increase the therapeutic effects of a medicine.